Economic goods or solidarity? Two different approaches to liberality - Giammusso, Salvatore (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2023)
In this paper, I will compare the Aristotelian and the Middle-Stoic concepts of liberality as stated by Cicero in the De Officiis, which refers to Panaetius. For both concepts, liberality is a principal virtue of socio-political life, but they start from different premises: the individual life in case of Aristotle, and social bonds in the case of Middle-Stoicism. I will try to point out that Aristotle, led by the dualism of reason and passions, is bound to think of liberality as an individual character virtue that prevails over the natural attachment to wealth and assets. Because of his dualism, Aristotle must exclude non-economic beneficence from the domain of liberality. In comparison, the Middle-Stoic approach is mainly based on the idea of sociability. This model does not undervalue goods, but it states that virtues mature from the balanced development of natural impulses, based on the combination of sociability and self-preservation, rather than from an ascetic effort. More particularly, the virtue of liberality originates from the social dimension of moral good. The liberal citizen can make virtuous use of money in certain cases, but he does not necessarily need it. The social sense is crucial, and it leads to the personal support of others, thereby creating and strengthening social bonds.